2018
DOI: 10.5858/arpa.2017-0150-oa
|View full text |Cite
|
Sign up to set email alerts
|

Factors Impacting the Performance Characteristics of Bile Duct Brushings: A Clinico-Cytopathologic Analysis of 253 Patients

Abstract: Context.-Literature on factors impacting bile duct brushings (BDBs) performance characteristics remain limited.Objective.-To capture the current state of daily practice with BDB sign-out.Design.-Two hundred fifty-three of 444 BDBs signed out by more than 7 cytopathologists, with histopathologic and/or clinical follow-up of at least 18 months, were examined.Results. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and accuracy of malignancy detection were 35%, 100%, 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 26 publications
0
21
1
Order By: Relevance
“…Additionally, logistic fit of clinically benign diagnosis is negatively correlated with these variables (results not shown).Site of malignancy, presence of a stent or calculus had no effect on cytological diagnosis. This is contrary to a study that reported lower sensitivity of cytological diagnosis in stented vs nonstented cases 14. This was explained to be due to the reluctance of cytopathologists in rendering a malignant diagnosis in context of anticipated reactive changes.…”
contrasting
confidence: 82%
See 2 more Smart Citations
“…Additionally, logistic fit of clinically benign diagnosis is negatively correlated with these variables (results not shown).Site of malignancy, presence of a stent or calculus had no effect on cytological diagnosis. This is contrary to a study that reported lower sensitivity of cytological diagnosis in stented vs nonstented cases 14. This was explained to be due to the reluctance of cytopathologists in rendering a malignant diagnosis in context of anticipated reactive changes.…”
contrasting
confidence: 82%
“…Other studies have also highlighted false-positive cytology in the setting of low-grade dysplasia, reactive papillary changes, postsurgical bile duct stenosis and primary sclerosing cholangitis. 5,10,14 Cytological criteria of malignancy are reported by Avadhani et al 15 One of the strengths of our study is that the endoscopists and cytopathologists were experienced and remained consistent during the entire period of the study. Our weakness is that fluorescence in situ hybridization (FISH) studies on cytology material was not performed in any of our cases.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…For bile duct brushing cytology, the known published ROM approaches 100% in the published literature; however, the various studies show a range of false‐positive results of 0% to 3% 35‐40 . The possible reasons for these false‐positive results include primary sclerosing cholangitis, 41 chronic pancreatitis, inflammatory conditions that mimic malignancy, or the presence of a bile duct stent that was unknown to the reporting cytologist or that the reporting cytologist did not consider when formulating the diagnosis 42 .…”
Section: Bile Duct Brushing Cytologymentioning
confidence: 99%
“…Nonetheless, the majority of biliary tract tumors that are diagnosed on bile duct brushing samples (BDBs) or intraductal biopsy either are pancreatic (pancreatic ductal adenocarcinoma) or biliary (intrahepatic and extrahepatic cholangiocarcinoma) in origin . Other sources of positive results are intraductal papillary neoplasms of the bile duct, primary tumoral intraductal neoplasms of the intrahepatic and extrahepatic biliary tree, and metastatic nonpancreatobiliary tumors from the upper and lower gastrointestinal tract, and even the lung . In addition to metastases from distant sites, the biliary tract also may be involved by direct extension of hepatocellular carcinoma (HCC).…”
Section: Introductionmentioning
confidence: 99%